การสร้างความรู้เพื่อการปรับเปลี่ยนตัวตนของเด็กและเยาวชนผู้ก้าวพลาด (KNOWLEDGE BUILDING FOR SELF-IDENTITY CHANGES OF MISS-STEPPING CHILDREN AND YOUTH) - เชาวตะ กรรฑิมา; พิพัฒน์เพ็ญ มณฑนา; ธรรมสัจการ วันชัย (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2015)
งานศึกษานี้ให้ความสำคัญต่อการทำความเข้าใจในตัวตนของเด็กและเยาวชนผู้ก้าวพลาดในมิติความเป็นคนชายขอบของสังคมที่พยายามสวมอัตลักษณ์เชิงลบจนทำให้เกิดการละเลยต่อศักดิ์ศรีความเป็นมนุษย์ การรู้เท่าทันต่ออัตลักษณ์ดังกล่าวจึงเป็นสิ่งสำคัญอันทำให้เด็กและเยาวชนที่ถูกมองว่าก้าวพลาด เกิดความตระหนักรู้ และต้องการปรับเปลี่ยนตัวตนเพื่อให้พวกเขามีพื้นที่ทางสังคม (social space) ดังนั้นการศึกษาจึงมุ่งเผยให้เห็นการปรับเปลี่ยนตัวตนของเด็กและเยาวชนเพื่อการดำรงอยู่ในสังคม รวมถึงการสร้างตัวตนของตนเองขึ้นมาใหม่ผ่านกระบวนการสร้างเทคโนโลยีแห่งตัวตน เพื่อให้พวกเขาสามารถกลับไปใช้ชีวิตอยู่ในสังคมอย่างมีศักดิ์ศรี เห็นคุณค่าในตนเอง และสามารถอยู่ร่วมกับบุคคลอื่นได้อย่างมีความสุข โดยใช้วิธีการศึกษาเรื่องเล่าของชีวิต (narrative approach) บนฐานกระบวนทัศน์สร้างสรรค์สังคม (social constructivism paradigm) ผลการศึกษาแสดงให้เห็นว่าการปรับเปลี่ยนตัวตนของเด็กและเยาวชนผู้ก้าวพลาดเกิดขึ้นจากการเรียนรู้โลก เรียนรู้สังคม เรียนรู้ตนเอง และเรียนรู้ผู้อื่น ความเข้มแข็งที่สร้างขึ้นจากตัวตน ทำให้เยาวชนกลุ่มนี้ตระหนักรู้ถึงภาพลักษณ์และความหมายที่สังคมนิยามให้ว่าเป็น “ผู้กระทำผิด” การรู้เท่าทันต่อความเชื่อของสังคมจึงส่งผลต่อการสร้างความรู้ของเด็กและเยาวชนว่าต้องปรับเปลี่ยนตัวตนใหม่ในเชิงบวกด้วยการสร้างอัตลักษณ์ที่ทำให้บุคคลอื่นยอมรับว่าเป็นส่วนหนึ่งของสังคม เรื่องเล่าจากประสบการณ์ชีวิตของเด็กและเยาวชนแต่ละคนจึงแสดงให้เห็นว่า พวกเขาสามารถสร้างตัวตนใหม่ได้หากได้รับความรัก ความไว้วางใจจากครอบครัวและเจ้าหน้าที่ การให้กำลังใจตนเองเพื่อสร้างตัวตนใหม่ด้วยการทำงานจิตอาสา การให้คำแนะนำเชิงบวกกับเพื่อนร่วมทางและการพยายามดำรงตัวตนใหม่ด้วยการปรับเปลี่ยนทัศนคติของตนเองในการมองโลก มองสังคม มองตนเองและมองผู้อื่น รวมถึงการสร้างความรู้ใหม่ให้ผู้อื่นในสังคมได้ร่วมเรียนรู้และรู้เท่าทันต่อความรู้ที่มีอยู่อย่างหลากหลายในอันที่จะปรับเปลี่ยนจากผู้ถูกกระทำไปสู่การเป็นผู้กระทำเพื่อการอยู่ร่วมกันอย่างเท่าเทียมและมีศักดิ์ศรี คำสำคัญ: การสร้างความรู้ ทักษะชีวิต อัตลักษณ์ปัจเจกบุคคล This study gives importance to understanding of self-identities of miss-stepping children and youth in the dimension of being marginal people of the society that tries to give them negative identities neglecting their human dignity. Awareness of such identities is, therefore, important for children and youth who are seen as miss-stepping to be aware and want to change their identities so as to gain social space. Thus, this study aimed to reveal self-identity changes among the children and youth in order to maintain their existence in the society. It also focused on rebuilding of self-identities through the process of self-technology building so that they could return to live in society with dignity, self-value, and ability to live with others happily. The study employed the narrative approach based on the social constructivism paradigm attaching importance to knowledge building to show self-identities of miss-stepping children and youth. The results of the study reflected that self-alteration of miss-stepping children and youth was due to their learning about the world, society, their selves, and others. The strength built from their own selves made them realize the image and meaning of “wrong doers” given to them by the society. Awareness of beliefs of the society affected knowledge building of the children and youth and made them realize that they had to change their self-identities and make them positive by building identities that were acceptable to others who would then see them as part of society. The narrations about life experiences of each of the children and youth showed that they could rebuild their self-identities if they were loved and trusted by their families and officers, had self-encouragement in order to rebuild self-identities by doing volunteer work, providing positive advice to their fellows, and trying to maintain their new identities by changing their attitudes towards the world, society, themselves, and other people. In addition, they could do so by building new knowledge for others in society so that they could join in learning and be aware of the diversified knowledge so as to make self-alteration from being done to, to being the doers in order to live with other people equally and with dignity. Keywords: Constructivism, Life Skills, Self Identity